Assessing spatial soil erosion under climate change using SWAT model in a semi-arid watershed of northeastern Tunisia - Fathia Jarray; Taoufik Hermassi; Haykel Sellami; Mohamed Ali Ben Abdallah; Mohamed Mechergui (Environmental Research Communications)
This study assesses the impact of climate change on streamflow and soil erosion dynamics in the Wadi Rmel watershed, using the Soil and Water Assessment Tool model under RCP4.5 and RCP8.5 scenarios. The model achieved an NSE of 0.61 and R ^2 of 0.66 during calibration and NSE of 0.83 and R ^2 of 0.85 during validation phase. Climate projections from EURO-CORDEX models were analyzed across three timeframes: short-(2021–2044), medium-(2045–2069), and long-term (2070–2100). Results show decreasing precipitation across all scenarios, with reductions below 10% in the short term and up to 40% in the long term. For the long term, maximum temperature is predicted to increase by 1.5–5.2 °C across all RCP8.5 scenarios. Streamflow is expected to decline from a baseline average of 0.27 m ^3 /s, dropping to 0.21m ^3 /s in the short term, with further reductions over time. The impact of climate change on soil erosion exhibits spatio-temporal variability, with reductions across sub-basins, influenced by factors such as vegetation cover and anthropogenic factors. While erosion rates are projected to decline in most areas, sub-basins with minimal vegetation cover, especially in the southwestern region, remain highly vulnerable. The highest erosion reductions are observed in central and northeastern sub-basins, linked to better vegetation and conservation measures. These findings reveal key gaps in land management and opportunities to strengthen resilience against future water challenges in semi-arid regions.